The Photoreaction of the Proton-Pumping Rhodopsin 1 From the Maize Pathogenic Basidiomycete Ustilago maydis - La Greca, Mariafrancesca; Chen, Jheng-Liang; Schubert, Luiz; Kozuch, Jacek; Berneiser, Tim; Terpitz, Ulrich; Heberle, Joachim; Schlesinger, Ramona (Frontiers in Molecular Biosciences, 2022)
Microbial rhodopsins have recently been discovered in pathogenic fungi and have been postulated to be involved in signaling during the course of an infection. Here, we report on the spectroscopic characterization of a light-driven proton pump rhodopsin (UmRh1) from the smut pathogen Ustilago maydis, the causative agent of tumors in maize plants. Electrophysiology, time-resolved UV/Vis and vibrational spectroscopy indicate a pH-dependent photocycle. We also characterized the impact of the auxin hormone indole-3-acetic acid that was shown to influence the pump activity of UmRh1 on individual photocycle intermediates. A facile pumping activity test was established of UmRh1 expressed in Pichia pastoris cells, for probing proton pumping out of the living yeast cells during illumination. We show similarities and distinct differences to the well-known bacteriorhodopsin from archaea and discuss the putative role of UmRh1 in pathogenesis.